A goodness of fit test for the multilevel proportional odds model. Issue 7 (9th August 2017) - Epasinghe, Nirodha; Sooriyarachchi, Roshini
ABSTRACT: It is essential to test the goodness of fit of the model before making inferences based on it. Multilevel modeling of ordinal categorical responses is not as developed as for continuous responses. Assessing model adequacy in terms of the goodness of fit with ordinal categorical responses is still being developed and no satisfactory tests are available so far. As a consequence of that, this study concentrates on developing such a goodness of fit test for Multilevel Proportional Odds models and to study the properties of the test.